Perancangan Website HIMASI STT Terpadu Nurul Fikri Menggunakan Pendekatan User Centered Design - Gian Nessie; Misna Asqia; Erlangga Rahimi (LPPM STT Terpadu Nurul Fikri, 2026)
The advancement of media technology has significantly influenced various sectors, including education. This development encourages student organizations such as the Information Systems Student Association (HIMASI) to adapt in delivering information more effectively. This study aims to design an official website for HIMASI as an information and communication medium to improve the effectiveness of information dissemination to students. The research method used is User-Centered Design (UCD), which consists of four stages: identifying the context of use, identifying user needs, developing design solutions, and evaluating the design. In the evaluation stage, a User Acceptance Test (UAT) was conducted with 26 respondents to assess the level of user acceptance and satisfaction. The results showed an average score of 92.46%, indicating a very high level of satisfaction. Based on these findings, it can be concluded that the designed website meets user expectations and is feasible to be implemented as an official platform for disseminating information by HIMASI.